Indonesian Legal Protection for Indonesian Citizens Who Have Been Sentenced by Criminal Punishments Abroad from an International Legal Perspective - Miracle Arthur Koraag; Gelar Ali Ahmad (NOVUM : JURNAL HUKUM, 2024)
Diplomatic protection by the Indonesian government is crucial in safeguarding Indonesian citizens facing legal problems under foreign jurisdictions. The cases of Siti Zainab and Tuti Tursilawati highlight the challenges faced by Indonesia in providing effective diplomatic assistance, where both citizens were sentenced to death with permanent legal force abroad. This research aims to analyze the resolution of criminal cases involving Indonesian citizens who have received final and binding criminal sentences abroad from the perspective of international law and international relations. The study employs a normative juridical method with a prescriptive approach, focusing on the analysis of legal norms to offer constructive solutions. The findings show that Indonesia’s diplomatic efforts in such cases are often hindered by limited access to legal processes in the host country and the principle of state sovereignty. Nonetheless, the Indonesian government undertakes several strategies to provide protection: (1) legal protection through consular assistance, (2) forming bilateral agreements on placement and protection of migrant workers, and (3) implementing a Single Channel Placement System (SPSK) through digital diplomacy. The study recommends strengthening diplomatic relations and proactive legal frameworks to enhance the state's ability to intervene effectively. By fostering mutual agreements and international cooperation, future cases similar to those of Tuti Tursilawati and Siti Zainab can be better addressed, ensuring the rights and safety of Indonesian citizens abroad are more effectively protected.